Performance of shallow tube well on groundwater irrigation in Tropical Lowland Rice Cultivation Area - Mohd Fauzie Jusoh; Mohamed Azwan Mohamed Zawawi; Hasfalina Che Man; Suzilawati Kamaruddin (Universiti Kebangsaan Malaysia, 2013)
Groundwater irrigation is one of the alternative methods to irrigate the paddy crops beside surface water. The use of shallow tube well for paddy irrigation is able to overcome water scarcity especially during dry season and off planting season in Malaysia. The performance of a shallow tube well was evaluated based on well efficiency and pump efficiency. The study was conducted at Seberang Perak Integrated Agricultural Development Area (Seberang Perak IADA). In this study, on-off automatic water controller was installed in the field and connected to the pump system which gave the command to the pump to irrigate the field during pre-saturation and normal growth plantation period. Water level inside the pumping well and cultivation plot was observed and recorded by the water level transducers. The result of the study showed that the pumping well is moderately productive with the well efficiency between 91 and 94%. The submersible pump efficiency was 87.5%. The potential yield of the pumping well was 450 m3day-1 and it was enough and sufficient to irrigate 1 ha of paddy field.